2017
DOI: 10.1504/jibed.2017.10009568
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intentions in an emerging industry: an exploratory study

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Some studies of artisan entrepreneurs have found that non-financial motives are significant, for example, personal happiness, independence (e.g. Alonso and Alexander, 2017; Chatterjee et al , 2017), the valuation of craft traditions or a desire to reinforce the surrounding region’s cultural identity (Ezeuduji, 2015; Vitasurya, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies of artisan entrepreneurs have found that non-financial motives are significant, for example, personal happiness, independence (e.g. Alonso and Alexander, 2017; Chatterjee et al , 2017), the valuation of craft traditions or a desire to reinforce the surrounding region’s cultural identity (Ezeuduji, 2015; Vitasurya, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of specific in-depth research on micro-entrepreneurs of craft beer the international literature contains only a relatively small number of contributions. Existing studies have focussed on entrepreneurs and micro-breweries in the United Kingdom (Danson et al, 2015;Ellis & Bosworth, 2015), USA (Alonso, 2011), Italy (Cannatelli et al, 2019), Sweden (Frisk & Johansson, 2018) and Australia (Watne et al, 2012;Watne & Hakala, 2013;Alonso & Alexander, 2017). Home brewing, the production of fermented beverages for (mostly) non-commercial purposes, is a hobby which is viewed as a seedbed or generator of business start-up intentions for craft breweries and microbreweries (Biraglia & Kadile, 2017).…”
Section: Theoretical Contextmentioning
confidence: 99%
“…In several investigations the transition of a hobby into a business is explained by the entrepreneurs' desire to share their passion for craft beer (Watne et al, 2012;Watne & Hakala, 2013;Alonso & Alexander, 2017;Frisk & Johannsson, 2018). The concept of 'entrepreneurial passion' is defined by Cardon et al (2009: 515) as "consciously accessible intense positive feelings experienced by engagement in entrepreneurial activities associated with roles that are meaningful for the self-identity of the entrepreneur".…”
Section: Theoretical Contextmentioning
confidence: 99%
See 2 more Smart Citations